2018
DOI: 10.1021/acs.cgd.8b01310
|View full text |Cite
|
Sign up to set email alerts
|

Organosilane-Assisted Synthesis of Hierarchical MCM-22 Zeolites for Condensation of Glycerol into Bulky Products

Abstract: Hierarchical micro-mesoporous MCM-22 zeolites were synthesized using hexamethyleneimine and organosilanes as structure directing agents, which enabled the formation of hierarchical zeolites with mesopores created by the voids left by the organosilanes after thermal treatment, without loss of the intrinsic microporosity of the zeolite. The addition of organosilanes to the synthesis medium reduced the incorporation of aluminum atoms into the zeolite framework, making the hierarchical zeolites more hydrophobic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…The global Si/Al molar ratios were determined by chemical analyses of the calcined samples using an Optima 8000 ICP-OES spectrometer. The H-form samples were acid digested, as described by Rodrigues et al 20 The suspension was kept at 150 °C for 1 h. Finally, the remaining sample was diluted with 100 mL of deionized water and analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global Si/Al molar ratios were determined by chemical analyses of the calcined samples using an Optima 8000 ICP-OES spectrometer. The H-form samples were acid digested, as described by Rodrigues et al 20 The suspension was kept at 150 °C for 1 h. Finally, the remaining sample was diluted with 100 mL of deionized water and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its high kinetic diameter (Table S1, 0.63 nm), solketal can hardly fit through fully grown zeolite pores. In a previous study of micro/mesoporous zeolites synthesized through the use of organosilanes as mesopore structuredirecting agents, Rodrigues et al 20 and Vieira et al 59 showed that hierarchical zeolites are more active than their purely microporous counterparts in reactions involving bulky molecules.…”
Section: Methodsmentioning
confidence: 99%
“…the methoxysilyl moiety can incorporate into MWW layers via covalent bonds with growing crystals while the bulky hydrophobic tail can restrict the ordered stacking of MWW layers along the c -axis. Although the strategy is seemingly simple, unfortunately only multilayered MWW nanosheets (15–60 nm) can be synthesized by using HMI and amphiphilic organosilane as dual-SDAs [ 33 , 34 ]. By using similar organosilane as co-SDA, comparable results are obtained in the cases for synthesizing Ti-MWW [ 35 ] and SAPO-34 zeolite nanosheets [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Pil‐Nb‐4.5 material shows steep adsorption between 0.12 and 0.4 of the p/p 0 region that was created by pillaring and is due to capillary condensation occurring in the mesopores. For the other pillared materials, the N 2 adsorption at low pressures is mainly due to the presence of micropores, while the MCM‐22 zeolite possesses a type I isotherm typical of materials with micropores …”
Section: Resultsmentioning
confidence: 99%